Patient and Therapist Perspectives on Treatment for Adults with PTSD from Childhood Trauma - Boterhoven de Haan, Katrina L. (J Clin Med, 2021)
This study aimed to explore patients’ and therapists’ experiences with trauma-focused treatments in patients with posttraumatic stress disorder from childhood trauma (Ch-PTSD). Semi-structured interviews were conducted with patients (n = 44) and therapists (n = 16) from an international multicentre randomised clinical trial comparing two trauma-focused treatments (IREM), imagery rescripting and eye movement and desensitisation (EMDR). Thematic analysis was used to identify key themes within the data. Patients and therapists commented about the process of therapy. The themes that emerged from these comments included the importance of the patients’ willingness to engage and commit to the treatment process; the importance and difficulty of the trauma work, observations of how the trauma focused therapy produced changes in insight, and sense of self and empowerment for the future. In addition, therapists made suggestions for optimising the therapist role in the trauma-focused treatment. This included the importance of having confidence in their own ability, confronting their own and their client’s avoidance and the necessity and difficulties of adhering to the treatment protocols. These reported experiences add further support to the idea that trauma-focused treatments, without a stabilisation phase, can be tolerated and deepens our understanding of how to make this palatable for individuals with Ch-PTSD.